Bronchial Epithelial Cells on the Front Line to Fight Lung Infection-Causing Aspergillus fumigatus - Bigot, Jeanne; Guillot, Loïc; Guitard, Juliette; Ruffin, Manon; Corvol, Harriet; Balloy, Viviane; Hennequin, Christophe (Frontiers in Immunology, 2020)
Aspergillus fumigatus is an environmental filamentous fungus that can be pathogenic for humans, wherein it is responsible for a large variety of clinical forms ranging from allergic diseases to life-threatening disseminated infections. The contamination occurs by inhalation of spores present in the air, and the first encounter of this fungus in the human host is most likely with the bronchial epithelial cells. Although alveolar macrophages have been widely studied in the Aspergillus–lung interaction, increasing evidence suggests that bronchial epithelium plays a key role in responding to the fungus. This review focuses on the innate immune response of the bronchial epithelial cells against A. fumigatus, the predominant pathogenic species. We have also detailed the molecular interactants and the effects of the different modes of interaction between these cells and the fungus.